Curcuminoids purified from turmeric powder modulate the function of human multidrug resistance protein 1 (ABCC1) - Chearwae W. (2014)
Multidrug resistance is a major cause of chemotherapy failure in cancer patients. One of the resistance mechanisms is the overexpression of drug efflux pumps such as P-glycoprotein and multidrug resistance protein 1 (MRP1, (ABCC1)). In this study, curcumin mixture and three major curcuminoids purified from turmeric (curcumin I, II, and III) were tested for their ability to modulate the function of MRP1 using HEK293 cells stably transfected with MRP1-pcDNA3.1 and pcDNA3.1 vector alone. The IC(50) of curcuminoids in these cell lines ranged from 14.5-39.3 microM. Upon treating the cells with etoposide in the presence of 10 microM curcuminoids, the sensitivity of etoposide was increased by several folds only in MRP1 expressing and not in pcDNA3.1-HEK 293 cells. Western blot analysis showed that the total cellular level of MRP1 protein level was not affected by treatment with 10 microM curcuminoids for three days. The modulatory effect of curcuminoids on MRP1 function was confirmed by the inhibition of efflux of two fluorescent substrates, calcein-AM and fluo4-AM. Although all the three curcuminoids increased the accumulation of fluorescent substrates in a concentration-dependent manner, curcumin I was the most effective inhibitor. In addition, curcuminoids did not affect 8-azido[alpha-(32)P]ATP binding, however they did stimulate the basal ATPase activity and inhibited the quercetin-stimulated ATP hydrolysis of MRP1 indicating that these bioflavonoids interact most likely at the substrate-binding site(s). In summary, these results demonstrate that curcuminoids effectively inhibit MRP1-mediated transport and among curcuminoids, curcumin I, a major constituent of curcumin mixture, is the best modulator.